2022
DOI: 10.3390/polym14163264
|View full text |Cite
|
Sign up to set email alerts
|

Fused Deposition Modeling Parameter Optimization for Cost-Effective Metal Part Printing

Abstract: Metal 3D-printed parts are critical in industries such as biomedical, surgery, and prosthetics to create tailored components for patients, but the costs associated with traditional metal additive manufacturing (AM) techniques are typically prohibitive. To overcome this disadvantage, more cost-effective manufacturing processes are needed, and a good approach is to combine fused deposition modeling (FDM) with debinding-sintering processes. Furthermore, optimizing the printing parameters is required to improve ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…In this step, the shrinkage factor ( S h ) was assumed to be equal to 17% and 21% in the plane and in the perpendicular (z) direction, respectively. Similar values have been reported in the literature for polyolefin-based filaments [ 30 , 31 , 40 , 41 , 47 , 50 , 51 ]. The OFS factors will be equal to 1.20 (OFS xy ) and 1.26 (OFS z ) in the plane and in the perpendicular direction, respectively.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…In this step, the shrinkage factor ( S h ) was assumed to be equal to 17% and 21% in the plane and in the perpendicular (z) direction, respectively. Similar values have been reported in the literature for polyolefin-based filaments [ 30 , 31 , 40 , 41 , 47 , 50 , 51 ]. The OFS factors will be equal to 1.20 (OFS xy ) and 1.26 (OFS z ) in the plane and in the perpendicular direction, respectively.…”
Section: Methodssupporting
confidence: 90%
“…These values led to the revision of the OFS values (see Equation (1)) as follows: 1.26 for the plane and 1.30 for the perpendicular direction. Large amounts of organics (used as the base matrix in the production of filaments) necessitate lengthy thermal cycles for de-binding processes in parts produced by FFF, which causes significant shrinkage in sintered parts and has also been designated as a limitation for the fabrication of ceramics by AM [ 30 , 31 , 40 , 41 ]. For these reasons, it is important to produce filaments with precise dimensional tolerances, manage over-extrusion, and assess how the presence of ceramic powder and moisture affect the susceptibility of organic components to degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously discussed in section 2.1, porosity stems from the ME production process, resulting in voids and poor interlayer bonding (Tosto et al, 2021) within the raster layers at the mesostructural/macrostructural level. Tosto et al (2022), who varied nozzle temperatures (240 and 2508C), layer heights (0.09 mm and 0.14 mm) and flow rate (100% and 110%) established that a decrease in nozzle temperature during ME fabrication increases air gaps in the green part, negatively affecting interlayer bonding between the rasters, which effectively induces residual stresses in the specimens. On the other hand, specimens produced with a higher flow rate (110%) and layer height (0.14 mm) were found to exhibit reduced discontinuities within the raster layers.…”
Section: Influence Of Process Parametersmentioning
confidence: 99%
“…Santamaria et al (2022) and Damon et al (2019) similarly observed voids of various sizes, corroborating the findings of the aforementioned authors; they noted that the porosity content of the sintered part depends on production parameters employed, including varying raster angle and build orientation. Meanwhile, Tosto et al (2022) found that an increase in layer height (from 0.09 mm to 0.14 mm) and flow rate (from 100% to 110%) improves the microstructural grain size of ME Steel 316L parts. The authors found specimens produced with higher layer height (0.14 mm) and flow rate (110%) to exhibit "a lower average grain area and narrower distribution" of microstructural grains.…”
Section: Introductionmentioning
confidence: 98%